Reading comprehension treatment development for high school students with autism spectrum disorder: Stakeholder considerations for feasibility. (January 2019) - Reutebuch, Colleen K.; Roberts, Garrett J.; Thompson, Julie L.; El Zein, Farah; Mize, Min; Weinberg, Aron N.; Austin, Christy R.; Forbis, Alex; Rodriguez, Kim
Highlights: Two reading comprehension treatments were examined for high school students with ASD. Focus groups were conducted with 39 participants including parents, educators, and school and district administrators. Treatments considerations regarding issues of social validity and quality of life are offered. Stakeholders affirmed the need for and value of the proposed treatments. Abstract: Background: We explored the potential benefits, possible challenges, and further considerations of two proposed academic interventions under development. These interventions target the reading comprehension of adolescents with autism spectrum disorder (ASD). These interventions were part of a comprehensive treatment package proposed to improve postsecondary outcomes for those with ASD transitioning to college, vocational training, and careers. Our purpose was to examine the reading comprehension treatments from the perspective of multiple stakeholders from whom buy-in is needed if treatments are to be used with confidence and fidelity. We aimed to better understand and address the issues that may limit the feasibility of implementation and thus treatment integrity and outcomes of our treatments prior to piloting them in typical high school settings. Method: We conducted six focus groups across two states. The 39 participants included family members of adolescents with ASD, school instructional and support staff members, and school and district administrators. The questions were semi-structured and open ended. A multistep, team-based approach was used to analyze focus group data. Results: We report on three major themes with supporting subthemes. Stakeholders affirmed the need for and value of the proposed academic component. However, they were unsure that the reading interventions would prove beneficial without the proper supports, understanding of ASD in place, and further enhancements. Conclusions: This study highlights the complexities of designing treatments for students with ASD across the spectrum. Stakeholder feedback is relevant and offers those designing and conducting school-based treatments considerations regarding issues of social validity and quality of life that can enhance or detract from treatment integrity and sustainability of the intervention. A rationale for gathering and using stakeholder feedback is provided to drive research design and implementation, along with recommendations for future research endeavors.